Alfred Billings Street papers - Street, Alfred Billings, 1811?-1881.
Volume containing poetry, prose, portraits, and a letter to George H. Treadwell.
Lawyer, poet, and librarian.
Collection material in English.
Keywords: Poetry; Treadwell, George H. -- Correspondence; Lawyers; Librarians; Poets